Using a Miniature Stapler to Divide a Mucosal Bridge at the Anastomosis after Gastric Pull-up for Iatrogenic Tracheoesophageal Fistula - Kawano, Takafumi; Muensterer, Oliver J. (European Journal of Pediatric Surgery Reports, 2018)
We report the first use of a miniature stapler to divide a mucosal bridge at the gastroesophageal junction after complex esophageal atresia (EA) repair. A 4-year-old girl was referred to our center after treatment of EA elsewhere. On our initial enodoscopy, a large iatrogenic tracheoesophageal fistula had formed, prompting us to perform a tracheoplasty and gastric interposition. One year after recovery, she had dysphagia with solid food. Upon endoscopy, a mucosal bridge was noted at the gastroesophageal anastomosis. This bridge was divided under endoscopy using a 5 mm miniature stapler. No complications were noted. Upon follow-up, she had no more complaints with solid food. Our report shows that the mucosal bridges may cause dysphagia after EA repair and can be safely divided using a miniature stapler.
Keywords: esophageal mucosal bridge; miniature stapler; iatrogenic tracheoesophageal fistula